New Horizons in Myeloproliferative Neoplasms Treatment: A Review of Current and Future Therapeutic Options - Domenico Penna (MDPI AG, 2021)
Philadelphia-negative myeloproliferative neoplasms (MPN) are aggressive diseases characterized by clonal proliferation of myeloid stem cells. The clonal process leads to excessive red cells production, platelets production, and bone marrow fibrosis. According to the phenotype, MPN can be classified as polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). MPN patients have shortened survival due to the increased risk of thrombosis, hemorrhages, and transformation to acute myeloid leukemia (AML). Prognosis is variable, with a shorter life expectancy in myelofibrosis. Currently, drug therapy can reduce symptoms, splenomegaly, and risk of thrombosis. Still, some patients can be resistant or intolerant to the treatment. At the same time, allogeneic stem cell transplant (ASCT) is the only treatment modality with the potential to cure the disease. Nevertheless, the ASCT is reserved for high-risk leukemic progression patients due to the risk of treatment-related death and comorbidity. Therefore, there is a need for new drugs that can eradicate clonal hematopoiesis and prevent progression to more aggressive myeloid neoplasms. Thanks to the better understanding of the disease’s molecular pathogenesis, many new potentially disease-modifying drugs have been developed and are currently in clinical trials. This review explores the most promising new drugs currently in clinical trials.